Humans and great apes cohabiting the forest ecosystem in central african republic harbour the same hookworms. - Hideo Hasegawa; David Modrý; Masahiro Kitagawa; Kathryn A Shutt; Angelique Todd; Barbora Kalousová; Ilona Profousová; Klára J Petrželková (Public Library of Science (PLoS), 2014)
Hookworms are important pathogens of humans. To date, Necator americanus is the sole, known species of the genus Necator infecting humans. In contrast, several Necator species have been described in African great apes and other primates. It has not yet been determined whether primate-originating Necator species are also parasitic in humans.The infective larvae of Necator spp. were developed using modified Harada-Mori filter-paper cultures from faeces of humans and great apes inhabiting Dzanga-Sangha Protected Areas, Central African Republic. The first and second internal transcribed spacers (ITS-1 and ITS-2) of nuclear ribosomal DNA and partial cytochrome c oxidase subunit 1 (cox1) gene of mtDNA obtained from the hookworm larvae were sequenced and compared. Three sequence types (I-III) were recognized in the ITS region, and 34 cox1 haplotypes represented three phylogenetic groups (A-C). The combinations determined were I-A, II-B, II-C, III-B and III-C. Combination I-A, corresponding to N. americanus, was demonstrated in humans and western lowland gorillas; II-B and II-C were observed in humans, western lowland gorillas and chimpanzees; III-B and III-C were found only in humans. Pairwise nucleotide difference in the cox1 haplotypes between the groups was more than 8%, while the difference within each group was less than 2.1%.The distinctness of ITS sequence variants and high number of pairwise nucleotide differences among cox1 variants indicate the possible presence of several species of Necator in both humans and great apes. We conclude that Necator hookworms are shared by humans and great apes co-habiting the same tropical forest ecosystems.